2019
DOI: 10.4081/ijfs.2019.7691
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigation on the microbiological quality of edible marine gastropods of the Adriatic Sea, Italy

Abstract: According to the European Legislation, marine gastropods placed unprocessed on the market must comply with the same requirements established for live bivalve molluscs but, being considered not filterfeeding and unable to concentrate fecal contaminants, they may be harvested outside the classified areas. Despite this statement, little scientific information is available on the microbiological quality of these animals. The aim of the present study was to investigate 28 batches of edible snails of the Adriatic Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In this study, the main qualitative traits of meat and the calcium shell content of the common sea snail species ( N. mutabilis ) were compared with those of the long sea snail ( H. reticulata ) whose population is increasing to the disadvantage of the most appreciated common species. To our knowledge, this paper is one of a few that deals with the quality traits of meat and the shell characterization of these gastropod species, captured in the Mediterranean Sea, which are mostly considered from the microbiological viewpoint [ 22 ]. Therefore, data were also compared with gastropods of other species and latitude distribution was investigated in a similar way to the current paper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the main qualitative traits of meat and the calcium shell content of the common sea snail species ( N. mutabilis ) were compared with those of the long sea snail ( H. reticulata ) whose population is increasing to the disadvantage of the most appreciated common species. To our knowledge, this paper is one of a few that deals with the quality traits of meat and the shell characterization of these gastropod species, captured in the Mediterranean Sea, which are mostly considered from the microbiological viewpoint [ 22 ]. Therefore, data were also compared with gastropods of other species and latitude distribution was investigated in a similar way to the current paper.…”
Section: Discussionmentioning
confidence: 99%
“…Although the samples considered in the present study were included only at the beginning and at the end of the sampling seasons and not throughout the year, the variable “season” was not significant for both gastropod species, except for ARA in the common snail where less yield was found in March. These two gastropod species, similar to most marine gastropods, are considered carnivorous with a degree of predatory activity that varies from actively seeking prey to grazing on sessile invertebrates to scavenging [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. This feeding behaviour can be affected by the substratum and may have affected the fatty acid profile in terms of n-3 PUFA and the n3/n6 ratio in the common sea snail.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, the bacterium was also present in a high abundance in the snails (88/427 colonies). To our knowledge, only one study on the detection of V. cholerae in snails is available [ 22 ]. Serratore et al reported that 28 batches of edible snails ( Nassarius mutabilis and Bolinus brandaris ) in the Adriatic Sea were negative for E. coli , Vibro vulnificus , and V. cholerae contamination [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only one study on the detection of V. cholerae in snails is available [ 22 ]. Serratore et al reported that 28 batches of edible snails ( Nassarius mutabilis and Bolinus brandaris ) in the Adriatic Sea were negative for E. coli , Vibro vulnificus , and V. cholerae contamination [ 22 ]. In this study, our results also provided additional evidence to demonstrate high detection frequencies of V. cholerae in fish species such as A. nobilis , C. auratus , and P. pekinensis , consistent with results of our prior research [ 6 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…This approach is tailored to the specific features of bivalves, and obviously, it is unsuitable for gastropods, because they lack two valves and obviously, intravalvular liquid. The viability of the batches of T. mutabilis was ascertained following an internal protocol, by spreading table salt on the animals, as NaCl results in an aversive stimulus promoting extroflexion of the foot and mucus production in viable animals [33]. For each batch, the viability was expressed as the percentage of living animals on the whole batch.…”
Section: Viability Of the Batches (Wps 1 2 And 3)mentioning
confidence: 99%